1899 N.Y. Laws 1341 - (:unkn) unknown (My University, 1899)
Ch. 603, § 1: Prohibited the selling or giving to a minor under the age of eighteen any pistol or other firearm. Also prohibited the selling or giving away any air-gun or spring-gun to minors under the age of twelve. Violators guilty of a misdemeanor.
Keywords: TRANSFER - MINORS